If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(n-8)=6(1-3n)
We move all terms to the left:
5(n-8)-(6(1-3n))=0
We add all the numbers together, and all the variables
5(n-8)-(6(-3n+1))=0
We multiply parentheses
5n-(6(-3n+1))-40=0
We calculate terms in parentheses: -(6(-3n+1)), so:We get rid of parentheses
6(-3n+1)
We multiply parentheses
-18n+6
Back to the equation:
-(-18n+6)
5n+18n-6-40=0
We add all the numbers together, and all the variables
23n-46=0
We move all terms containing n to the left, all other terms to the right
23n=46
n=46/23
n=2
| 3+2x=15-5x | | 7(2x–30)=84 | | 27v-160-32v=-2 | | 7x+12=11x+6 | | 3(2x-4)-6x=-6x-12 | | 3x+9=15 | | 300x+5=240x+125 | | -6y+4=-8y | | -5x=(4/5x2) | | -18p=-19p+15 | | 2/x=-2 | | -2|2.2x-3.3=-6.6 | | 8+18h+3h=19h-2 | | 2(3x-4)=2(2x+1) | | -3g=15 | | 0.02x=325 | | -12r+10=-40r+10 | | 6+13x+29x+6=180 | | 3(a-5)=2(4a-1 | | 20w-4-18w=10 | | 32x+72=40x–56 | | 2z/7+2=—1 | | 3(1/2x+6)=12 | | 5x+19)+6x+1=180 | | 2(4-x)+x=3x-12 | | 5x+11=134 | | 0=14x2-17x-6 | | 2(5x+9)+12=110 | | 4/5(10x+20)-7=5x+15 | | -3(x-5)=3(x+5) | | -2(x+7)=-2(3x-2)+8x | | 2(2m-3)=7(m+6) |